A Holistic Framework for Conceptualizing Hospital Service Quality. (March 2017) - Swain, Swapnarag; Kar, Nirmal C.
Managing service quality has always been one of the most important areas of concern in hospitals. With the advancement of lifestyle, education and awareness among consumers, they are becoming more and more demanding. This is the reason why hospitals are spending huge amount in managing service quality that leads to satisfaction among patients and ultimately contributes in brand building. Thus the first and most important consideration is to determine and understand the various dimensions of service quality in the perspective of hospitals. Many researchers have studied these dimensions of hospital service quality but none of the studies cover all the possible areas of service quality management in a hospital set-up. This study aims to critically review the work of different researchers to determine and define the dimensions that would cover all areas of service quality management in hospitals. This study has developed a conceptual framework of hospital service quality by identifying 15 different dimensions: infrastructure, resource availability, waiting time, food, clinical procedures, administrative procedures, price, trustworthiness, information availability, patient safety, continuity, personalized attention, staff attitude, quality of outcome and religious needs. These 15 dimensions are further clubbed under three broad dimensions such as 'infrastructural dimension', 'procedural dimension' and 'interactional dimension'. These dimensions can be used for measuring service quality management practices followed across different categories of hospitals like public and private or multi-specialty and super-specialty.